The hegemonic gender order in politics - De Simone, S. (2018)
Purpose – Despite the ongoing increase of women in the top positions, they are still underrepresented in politics. The studies that primarily focus on women’s underrepresentation in politics neglect the role of gender as a category that structures and makes sense of social practices. The purpose of this paper is to investigate the mechanisms that regulate the contemporary gender order in politics through discourse analysis and the contribution of the critical feminist perspective. Design/methodology/approach – The study is based on 30 biographical interviews with Italian politicians and focuses on the account of their political experiences and on the meanings attributed to these. Findings – The results of this paper underline the tendency to either absolve or blame women for gender inequality in politics through different interpretative repertoires: “Women’s disinterest toward politics,” “Politics as masculine context” and “Politics–family unbalance.” The analysis allowed to unravel the way in which the discursive practices create and reproduce the hegemonic gender order in politics. Research limitations/implications – The research is limited to 30 qualitative interviews, and so results cannot be generalized. Practical implications – The findings of this paper highlight the importance of exploring issues relating to the gender gap in politics and stress the need to implement actions to promote gender equality in politics. Originality/value – The paper contributes to an understanding of women’s underrepresentation in politics and offers causes for reflection on a phenomenon that has profound implications for our society. Keywords Gender, Discourse analysis, Politics, Critical feminist perspective Paper type Research paper